Sample Canister Capture Mechanism for Mars Sample Return: Functional and environmental test of the elegant breadboard model. (December 2015) - Carta, R.; Filippetto, D.; Lavagna, M.; Mailland, F.; Falkner, P.; Larranaga, J.
Abstract: The paper provides recent updates about the ESA study: Sample Canister Capture Mechanism Design and Breadboard developed under the Mars Robotic Exploration Preparation (MREP) program. The study is part of a set of feasibility studies aimed at identifying, analysing and developing technology concepts enabling the future international Mars Sample Return (MSR) mission. The MSR is a challenging mission with the purpose of sending a Lander to Mars, acquire samples from its surface/subsurface and bring them back to Earth for further, more in depth, analyses. In particular, the technology object of the Study is relevant to the Capture Mechanism that, mounted on the Orbiter, is in charge of capturing and securing the Sample Canister, or Orbiting Sample, accommodating the Martian soil samples, previously delivered in Martian orbit by the Mars Ascent Vehicle. An elegant breadboard of such a device was implemented and qualified under an ESA contract primed by OHB-CGS S.p.A. and supported by Politecnico di Milano, Department of Aerospace Science and Technology: in particular, functional tests were conducted at PoliMi-DAST and thermal and mechanical test campaigns occurred at Serms s.r.l. facility. The effectiveness of the breadboard design was demonstrated and the obtained results, together with the design challenges, issues and adopted solutions are critically presented in the paper. The breadboard was also tested on a parabolic flight to raise its Technology Readiness Level to 6; the microgravity experiment design, adopted solutions and results are presented as well in the paper. Abstract : Highlights: Manufacturing Assembly Integration and Test of a capture mechanism breadboard for Mars Sample Return mission. Breadboard implementation and qualification. On ground functional and environmental test of the breadboard to raise the mechanism TRL to 4. Parabolic flight test campaign to raise the mechanism TRL to 6. Demonstration of mechanism design functionality in relevant environment and full scale, TRL up to 6.